The role of patents in cartel stability - Prokop, Jacek (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Oligopolistic firms entering a collusive agreement often face the prisoner dilemma problem which makes such agreements inherently unstable. There has been a wide discussion in the literature on a variety of solutions to stabilize cartel arrangements. Only recently, it has been pointed out that patents could play an important role in cartel creation and functioning. However, there is a need for a formal modelling to better understand the role of patents in market competition. Aim: In this paper, we consider the impact of patent rights on the competition of duopolists in the final product market. We assess the incentives of firms holding essential patents to create a cartel. Our main objective is to investigate the role of patents in cartel stability. Results: Using game-theoretical approach, we show that it is beneficial for the patent-holding duoplists to form a cartel. Moreover, it is demonstrated that the existence of patents may help eliminate the prisoner dilemma problem faced by the participants of collusive agreement and significantly contribute to cartel stability. These conclusions suggest that patents may play an important role in restricting market competition.